PENGARUH KESEHATAN DAN KESELAMATAN KERJA TERHADAP KINERJA KARYAWAN BAGIAN UPT KRU KERETA API PT. KERETA API INDONESIA (PERSERO) DAERAH OPERASI 4 SEMARANG - Alfanandu Arya Widagda; Rodhiyah Rodhiyah; Sendhang Nurseto (Universitas Diponegoro, 2014)
Employee performance is affected by many factors, one of which is occupational health and occupational safety. This study aims to determine the condition of occupational health, occupational safety, employee performance and influence of occupational health and safety toward the employee performance of the Unit Train Crew 4th Operation Teritory Of Semarang Co.,Ltd, by taking 67 employees as respondents. Analysis techniques using validity test, reliability test, simple linear regression, multiple linear regression, t-test, and f-test supported by SPSS version 17 for Windows. Judging from the results of the calculation of the variable categorization table, occupational health, occupational safety, employee performance are in the good condition. From the calculation results of t-test, there is the influence of occupational health toward employee performance, and occupational safety toward employee's performance. From the calculation results of test-f, there is the influence of the occupational health and safety toward employee's performance. The company need to improve occupational health, especially by increase the availability of health insurance and health insurance benefits. Safety needs to be improved, especially by increase the availability of PPD and P3K complement and provide socialization and tighten controls on the use of PPD.